Fenología y dinámica de Arthropoda en tomate ( Lycopersicon esculentum Mill ) en el Bajo Mayo - San Martín - Turkowsky Torres, José Alfredo (1997)
The purpose of this research was to determine the Order and Family of certain species of harmful and beneficial arthropods, and correlate their incidence in different stages of the cultivation of tomatoes . The experiments were done on land belonging to Mr . Eduardo Ramirez Flores in the Province and Region of San Martín District of Morales, Sector Cocopa. The soil texture was sandy clay with a pH of 7,5; 1,17 % organic material (poor ), located at an elevation of 350 meters above sea level with precipitation of 1 200 mm anually. The work was done in an area of 196 m2 divided in to 5 sub-sections of 2 m2 with 10 plants per section, totaling 50 plants . Th "T" test was used for the statistical analysis verifying a significant presence of Order and Family of harmful and beneficial arthropods with a probability of 0,05 %. The fenological development of the tomatoes indicated the presence of harmful and beneficial arthropods from the second to the fifth growth stages with lesser populations in the sixth stages . The majority of the harmful arthropods belonged to the Orders Homoptera, Coleoptera, Lepidoptera and Orthoptera; with lesser populations of Hymenoptera and Hemiptera . The beneficial arthropods belonged to the orders of Aracnida and Diptera with lesser populations of Hemiptera and Odonata.